2014
DOI: 10.1111/caim.12084
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing and Innovative Work Behaviour in Healthcare: A Micro‐Level Investigation of Direct and Indirect Effects

Abstract: This study presents a micro‐level investigation that provides new insights into how employees' knowledge sharing affects their own innovative work behaviours (IWBs). Our study posited three mechanisms linking an individual's knowledge sharing behaviours to his or her own IWBs: (i) a direct effect whereby the act of sharing elicits a recombination and translation of knowledge that facilitates innovation; (ii) an indirect effect whereby knowledge sharing creates social conditions (i.e., reciprocation with new kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
220
3
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(257 citation statements)
references
References 113 publications
(160 reference statements)
14
220
3
20
Order By: Relevance
“…The present study confirms the findings of Radaelli, Lettieri, Mura, and Spiller (2014), who posited that idea promotion is enabled by knowledge-sharing behaviour. While the sharing of best practices in the research by the latter authors promoted idea generation among healthcare professionals in hospice and palliative care organisation, this has now also been confirmed in the context of technology students in higher education.…”
Section: Knowledge-sharing Behaviour As Mediatorsupporting
confidence: 91%
“…The present study confirms the findings of Radaelli, Lettieri, Mura, and Spiller (2014), who posited that idea promotion is enabled by knowledge-sharing behaviour. While the sharing of best practices in the research by the latter authors promoted idea generation among healthcare professionals in hospice and palliative care organisation, this has now also been confirmed in the context of technology students in higher education.…”
Section: Knowledge-sharing Behaviour As Mediatorsupporting
confidence: 91%
“…In addition, research has found that employee's knowledge sharing has a significant and positive influence on their innovative work behavior [29,48,49]. Radaelli et al [29] explained that when employees share their knowledge, they are more likely to elaborate, integrate, and translate information rather than simply passing on information to recipients.…”
Section: The Effects Of Work Engagement and Knowledge Sharingmentioning
confidence: 99%
“…Radaelli et al [29] explained that when employees share their knowledge, they are more likely to elaborate, integrate, and translate information rather than simply passing on information to recipients. This exercise promotes employee involvement in innovative work behavior, including searching for opportunities for change and applying new ideas to existing organizational practices.…”
Section: The Effects Of Work Engagement and Knowledge Sharingmentioning
confidence: 99%
See 2 more Smart Citations